Subtle bodies : representing angels in Byzantium - Peers, Glenn (Transformation of the classical heritage, 2001)
Explores the strategies used by Byzantine artists to represent the incorporeal forms of angels and the rationalizations in defence of their representations mustered by theologians in the face of iconoclastic opposition. These problems of representation provide a window on Late Antique thought.